PENGEMBANGAN BAHAN AJAR FLIPBOOK BERBASIS PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS V PADA MATERI IPAS - Nur Faridatus Solehah; Tri Suminar; Tri Joko Raharjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop and evaluate the effectiveness of a digital Flipbook teaching material based on Problem Based Learning (PBL) to improve the critical thinking skills of fifth-grade students at SDN Pesantren and SDN Ngadirgo 02, Semarang. The research employed a Research and Development (R&D) method using a simplified version of the Borg & Gall model in eight stages. The results showed a significant improvement in students’ critical thinking skills, with the average posttest score reaching 78.98, compared to the pretest score of 53.70. The N-Gain scores were 0.46 in Class A and 0.48 in Class B, both categorized as moderate. The product was deemed highly feasible based on expert validation: language expert (95%), media expert (96%), content expert (95%), and teaching practitioner (93%). Therefore, the PBL-based Flipbook was proven to be effective in enhancing students’ critical thinking skills in IPAS learning.